Decision Support System for Determining Tutoring Institutions for SNBT Preparation Using the Weighted Product Method - Batubara, Shabrina Husna; Maulana, Sandy Andika; Harahap, Wahyu Abadi; Niska, Debi Yandra (Journal of Computer Science Advancements, 2024)
There are several stages in choosing a state university, one of which is through the Joint Selection for State University Admission. To prepare for this, many SNBT candidates attend Learning Guidance Institutions. Learning guidance is a service or educational program designed to help students understand the subject matter taught in school. Its main goal is to improve students' academic abilities through various methods. This research aims to develop a Decision Support System (DSS) using the Weighted Product (WP) method to help choose the most appropriate Tutoring Institution. The system is designed to help parents and prospective students make decisions that suit their needs, taking into account factors such as teaching quality, facilities, and costs. With this DSS, it is hoped that the process of selecting Tutoring Institutions can be carried out more efficiently and accurately so that prospective participants can prepare themselves better to face SNBT. Based on the completed case study, the highest preference value is obtained by Adzkia (A4) with a value of 0.231, while the lowest preference value is Ganesha Operation (A1) with a value of 0.168. The results from the DSS built, and the manual calculations, show the same values.